2012
DOI: 10.1038/nature11354
|View full text |Cite
|
Sign up to set email alerts
|

Interaction landscape of membrane-protein complexes in Saccharomyces cerevisiae

Abstract: Macromolecular assemblies involving membrane proteins (MPs) serve vital biological roles and are prime drug targets in a variety of diseases. Large-scale affinity purification studies of soluble-protein complexes have been accomplished for diverse model organisms, but no global characterization of MP-complex membership has been described so far. Here we report a complete survey of 1,590 putative integral, peripheral and lipid-anchored MPs from Saccharomyces cerevisiae, which were affinity purified in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
221
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(230 citation statements)
references
References 36 publications
9
221
0
Order By: Relevance
“…The comprehensive identification of proteins associated with transmembrane receptors is technically problematic due to the harsh protein extraction conditions needed to solubilize the receptors for affinity purification, to which the relevant complexes are relatively labile (19,20). Compared with alternative strategies of using short peptide motifs corresponding to receptordocking sites, we expected that the "full-length" cytoplasmic domain with physiologically relevant modifications could recruit more critical downstream proteins associated with an activated receptor (7,8).…”
Section: Resultsmentioning
confidence: 99%
“…The comprehensive identification of proteins associated with transmembrane receptors is technically problematic due to the harsh protein extraction conditions needed to solubilize the receptors for affinity purification, to which the relevant complexes are relatively labile (19,20). Compared with alternative strategies of using short peptide motifs corresponding to receptordocking sites, we expected that the "full-length" cytoplasmic domain with physiologically relevant modifications could recruit more critical downstream proteins associated with an activated receptor (7,8).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, Msp1 serves to enhance the fidelity of protein localization. into a hexameric structure akin to other AAA-ATPases (14). Unlike Cdc48, which contains two ATPase domains that form a double-ring structure (15,16), Msp1 contains a single ATPase domain composed of canonical Walker A (P-loop) and B (DExx) motifs (Fig.…”
Section: Significancementioning
confidence: 99%
“…Despite a growing trend in deposition of large protein interaction data sets from isolation studies and components identified by proteomics approaches, as described later in this publication (5,6); Y2H studies have yielded a rich source of protein interaction data (supplemental Tables S1, S2) over the past three decades. Y2H determines physical interaction between two proteins (binary interactions) by means of transcriptional activity (7).…”
mentioning
confidence: 99%